Peran Pendidikan Non Formal Dalam Implementasi Program Merdeka Belajar Ada Warga Belajar Sanggar Kegiatan Belajar (SKB) Kabupaten Lombok Timur - Yani, Ahmad (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2023)
Non-formal education is a planned and systematic educational path carried out by the government and the community independently to achieve learning goals. It aims to be able to keep pace with the increasingly rapid development of the world, and answer the needs of situations and conditions, including in the current era of independent learning. The independent learning education policy was implemented by the Minister of Education and Culture as a response to the needs of the education system in the era of revolution 4.O. The method used is a qualitative approach with a secondary data matrix, documentation is then analyzed through the stages of data reduction, data presentation, and conclusions. The role of non-formal education contributes to the success of the independent learning program for learning center learning residents. The independent learning program is not enough to only focus on school education. Therefore, non-formal education with personally regulated regulations provides additional learning facilities for learning residents in the implementation of independent learning in the east Lombok learning activity studio.